Pemantauan dan Evaluasi Sasaran Mutu untuk Efektivitas Implementasi Sistem Manajemen Mutu ISO 9001:2015 di PT X - Ongko, Biondi; Sutapa, I Nyoman (Jurnal Titra, 2019)
This research’s purpose is to discuss the result in achieving quality goal from every department in PT. X. Process of monitoring for guality goal can be assisted by an application like Excel in the form of Dashboard  This design of monitoring system use dashboard, that could show progress or movement in achieving goal, so it enable the top management to detect any possible sign that the quality goal not achieved, and could take an immediate action to solve the problem, in order to ensure the progess ini achieving goal stay on the right track. Dashboard’s purpose is to showcase the final result in achieving goal that is displayed in the form of picture that is more attractive than only form of number. This program needs data to be inputted regularly, so it can be for this monitoring system use dashboard that needs data to be input regularly so that the data can be processed automatically because it is designed with a formula. Result of monitoring and evaluation for quality goals, nine of total eleven quality goal were achieved.